QR code-based ECG signal encryption/decryption algorithm - Mathivanan, P.; Ganesh, A. Balaji; Venkatesan, R. (Cryptologia, 2019)
The paper presents a novel and enhanced bio-signal (ECG) cryptographic technique in which a QR code has been successfully utilized as a data container. The bio-signal encryption process considers ECG samples in the form of integers in order to create corresponding binary pair sequences that are converted as equivalent ciphertext information. Subsequently, the generated ciphertexts are transformed into QR code by using a QR code generator/reader in order to ensure further security. The encryption process generates a binary key for each binary pair that will be used during signal decryption. The imperceptibility of a reconstructed ECG signal is evaluated by analyzing performance metrics in terms of PSNR and PRD values. The average PSNR values are found to be above 42 dB, whereas PRD values observed were less than 3.43 percent. It is further proved that the proposed technique can encrypt a maximum of 226 kb of diagnose data by using merely seven QR codes.